Perancangan Peningkatan Produktivitas pada Lini Produksi XS-156 di PT Schneider Electric Manufacturing Batam (SEMB) - Carlos Checa Putra Hardiyanto; Jani Rahardjo (Jurnal Titra, 2022)
This research was conducted to improve productivity on XS-156 production line at PT Schneider Electric Manufacturing Batam. Productivity improvement can be done by reducing design time and defect rate on the production line. Based on the actual data, there is an increase in DT on cell-03 by 42.7% and often occur problems with cables coming out from the diffuser. Method used to improve productivity on the production line is DMAIC. This method is used to analyze root causes and design improvements for the existing problems. Root caused analysis is done by using a fishbone diagram. The root caused can be found on six factors which is man, machine, method, measurement, material, and environment. Problems that have the biggest impac are cables coming out from the diffuser and jig loose. The analytic result is used to make improvements to the existing problems. Improvements that can be done is determining the appropriate cable length and tightening the jig. In addition, there is a decrease in DT by 62.6%.